INTRAVENOUS CORTICOSTEROID EFFECTS ON SUPERIOR AND INFERIOR RECTUS MUSCLE IN THYROID EYE DISEASE: Oral Presentation - Observational Study - Resident - Milzan Murtadha (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Intravenous corticosteroid has been used in management of Thyroid Eye Diseases (TED) which was an autoimmune inflammatory disease of the orbital tissues and the eyes. Previous study has shown benefits of intravenous corticosteroid therapy on TED but there was need of quantitative measure to assess the effect of intravenous corticosteroid therapy on extraocular muscle. This study aimed to report the effect of high-dose intravenous corticosteroid pulse therapy on superior and inferior rectus muscle and providing data distribution of active TED before and after therapy Methods : Retrospective analyses were used in the data collection of patients with active TED underwent high- dose intravenous methylprednisolone pulse therapy regiment 500mg every week for six consecutive weeks at Sardjito Eye Centre between January and December 2022. Ophthalmological investigation and quantitative computed tomography (CT) scan of the orbit were performed before and after corticosteroid pulse therapy and demographics data were presented in tables and graphs Results : This study included 62 eyes of 31 patients (61,3% female) with mean age of 37.8±13.47 years old. The mean thickness of Superior Rectus (SR) muscle before therapy were 4.12±2.20 mm and decreased to 3.64±1.50 mm post therapy. The mean thickness of Inferior Rectus (IR) muscle before therapy were 4.45±1.80 mm and decreased to 4.26±1.63 mm post therapy. There was significant difference in mean ΔSR -0.47±1.84 mm (p=0.046) but not in ΔIR -0.18±1.69 (p=0.381) Conclusion : The treatment of Thyroid Eye Disease (TED) with high dose intravenous corticosteroid is safe and effective in reducing extraocular muscle tissue thickness with minimal side effects.